Modeling red deer functional connectivity at a regional scale in a human-dominated landscape - Urbina, Loreto; Fischer, Claude; Ray, Nicolas; Lehmann, Anthony (Frontiers in Environmental Science, 2023)
Ecological connectivity is a key attribute of landscapes and indicates how landscapes facilitate or impede movement. It is an essential criterion to consider in the design of green infrastructures (GI) when landscape planners and managers deal with population viability, which in part depends on the movement capacities of organisms. Our goal is to inform about the conservation value of land parcels to maintain or enhance connectivity. For this, we developed a red deer functional connectivity model at a regional scale. We focused our study on this large mammal species inhabiting the Greater Geneva agglomeration between Switzerland and France. Our study site is dominated by forested mountains and lowlands, which are highly fragmented by human infrastructures and agricultural lands. We used GPS location data from fifteen red deer to parameterize the habitat resistances with a multivariate analysis. To predict connectivity at regional scale, we used local expert knowledge to design a graph-based landscape. Then we used electric circuit theory with the Circuitscape software to detect pinch points and map corridors, using the set of resistances parameterized with experimental data and the putative core areas and links identified with the help of expert knowledge. We obtained a map that highlights suitable regional habitat patches and corridors or connectivity pinch points potentially used by red deer between the mountains and the lowlands, ratifying the importance of the transfrontier collaboration when implementing the GI. The obtained results are used to assist landscape managers and planners in their effort to include functional connectivity in the prioritisation of the GI infrastructure across the region.